PENTINGNYA KONSELING RELIGI UNTUK MENGATASI KENAKALAN REMAJA: Konseling Religi - Lita Amelia; Diaz Robigo; Hasanah Imania; Dion Mart S; Penni Natalia S; Affan yusra (BULLET : Jurnal Multidisiplin Ilmu, 2022)
This literature review discusses the importance of religious counseling to overcome juvenile delinquency. The method used is descriptive analysis, namely by exploring all sources related to religious counseling as an effort to overcome juvenile delinquency. By using data collection techniques, which in this research is a literature study (Library Research) where library research is an activity to collect data related to research through books, scientific journals, articles and literature and other publications that can be used as sources for research to be studied by the author. The purpose of this research is to overcome the problem of delinquency in adolescents with the method of religious counseling. At a young age, they want to find their identity and want to be considered their existence in the community by doing various things, both positive and negative things which are commonly referred to as juvenile delinquency. Adolescent deviant behavior is a serious problem that must be dealt with quickly to save future nations. Religious counseling is one of the efforts that can be used in overcoming problems in adolescents, where religious counseling means helping someone by realizing himself as a person who fully achieves satisfaction in life in this world and in the hereafter in accordance with Islamic provisions. So it is hoped that in the future by using the religious counseling method, juvenile delinquency can be eradicated and can also form a better personality again according to religious norms and become quality teenagers who are religiously obedient.